Penggunaan E-banking dalam Sistem Informasi Manajemen Perbankan Syariah - irmayani, irmayani; Irwan Padli Nasution, Muhammad (Banque Syar’i: Jurnal llmiah Perbankan Syariah, 2023)
The purpose of this study is to determine the use of e-banking in Islamic banking and how to use good e-banking to keep customer data safe. It can be seen today that all access can be easily loaded via a gadget or smartphone. The development of Islamic banking has recently successfully become the spotlight of all levels of national banking. The government is no eception, which is now also providing encouragement for the advancement of Islamic banking. As with Bank Indonesia’s plan as a financing alternative in the Islamic financial market. And even the government has also officially launched the Indonesian Sharia Economic Master Plan MEKSI 201-202, as a pioneer for Islamic banks to have the opportunity to enter the ranks of the 10 largest banks in Indonesia. Thus, in conducting Islamic banking activities in cooperation with the field of information technology to build a syariah banking information system by loading a special application that can simplify all eisting transaction processes in Islamic banking. The implementation of e-banking or electronic banking is an application of Islamic banks to answer the desires of customers who want fast, safe, comfortable, inepensive service that is available at any time 2 hours day, 7 days week and can be accessed from anywhere, from cellphones. , computers, laptops and so on